The Factors of the Wise Man in the concepts of Theravāda Buddhism - keo, Ratanak; LeekaAsst, Jaras; Thongpan, Suwin (Journal of Buddhist Education and Research (JBER), 2018)
The objective of this text is to study of “The factors of wise man in Theravāda Buddhism”. This is aimed (1) To study the factor of wise man in the concepts of Theravāda Buddhism, (2) To analyze the concept of factors of wise man in Theravāda Buddhism. In this text, the four factors: Su, Ci, Pu and Li are basic root to develop the man to become the wise man in the perspectives of worldly knowledge. Su is abbreviated from sutta means listening or learning which make the learned man. Ci is abbreviated from cinta means thinking which makes the thoughtful man. Pu is abbreviated from pucha means asking or inquiring which makes considered man. And Li is abbreviated from likhita means taking note which makes memorable man. Thus su, ci, pu and li (listening, thinking, asking and taking note) are basis root of wise man. The factors of wise man are to create the knowledge of the man is considered as scholar or wise man who is full of the worldly knowledge for solving the problems of life and living happily. So the factors of wise man is creating of wisdom for man to solve the problems of life and finding the real happiness.